Community Supports After Surviving Extremely Low-Birth-Weight, Extremely Preterm Birth: Special Outpatient Services in Early Childhood - Hintz, Susan R. (2008)
OBJECTIVE: To determine special outpatient services (SOS) use, need, associated factors, and neurodevelopmental and functional outcomes among extremely preterm infants at 18 to 22 months’ corrected age. DESIGN: Retrospective analysis. SETTING: National Institute of Child Health and Human Development (NICHD) Neonatal Research Network. PARTICIPANTS: Infants younger than 28 weeks’ gestational age who had been born weighing less than 1000 g at an NICHD Neonatal Research Network center from January 1, 1997, to December 31, 2000, and who were receiving follow-up at 18 to 22 months’ corrected age. INTERVENTIONS: Questionnaires were administered at the 18- to 22-month follow-up visit regarding SOS use since hospital discharge and the current need for SOS (social work, visiting nurse, medical specialty, early intervention, speech and language services, occupational therapy and physical therapy, and neurodevelopmental and behavioral services). MAIN OUTCOME MEASURES: The use of and need for SOS were analyzed by gestational age. Logistic regression analysis identified factors independently associated with the use of more than 5 services and with the need for any services. RESULTS: Of 2315 infants, 54.7% used more than 3 SOS by 18 to 22 months, and 19.1% used 6 to 7 SOS. The need for any SOS was reported by approximately 37%. The following variables that were commonly associated with adverse neurodevelopmental outcomes were also associated with the use of more than 5 SOS: sepsis, birth weight, postnatal corticosteroid use, bronchopulmonary dysplasia, and cystic periventricular leukomalacia or grade 3 or 4 intraventricular hemorrhage. Male sex was associated with the need for any SOS. Although high SOS use was more likely among children with adverse neurodevelopmental outcomes, a reported need for SOS was common even among those with mild developmental impairment (39.7%) and mild cerebral palsy (42.2%). CONCLUSIONS: High SOS use is common, has identifiable neonatal risk factors, and is associated with neurodevelopmental impairment. Extremely preterm survivors have substantial need for community supports regardless of their impairment level. Efforts to improve comprehensive delivery of family-centered community-based services are urgently needed.